Finite element analysis of anterior cruciate ligament reconstruction techniques: A comparison of the mechanical properties of all-inside fixation and traditional fixation - Chen, Xiaodong; Xue, Changguo; Li, Kuanxin; Mu, Kecheng; Yao, Cheng; Wang, Zhiyan; Chen, Hongzhi; Zhang, Jun (Frontiers in Bioengineering and Biotechnology, 2024)
The main aim of this study was to investigate the mechanical properties of the anterior cruciate ligament (ACL) and its attachments following reconstruction with the all-inside technique post-ACL injury. Methods: Knee joint computed tomography data were collected from healthy volunteers, and knee joint models were created using Mimics software. We established a normal knee joint model, an all-inside reconstructed ACL model, and a traditional reconstructed ACL model. A tensile force of 134 N and a bending moment of 5 N/m were applied to the anterior aspect of the proximal tibia in these models. The knee joint underwent external rotation, internal rotation, varus, valgus, flexion, and extension under these loads. The stress magnitude and distribution on the ligament or graft and its attachments were observed under different loading conditions. Results: Under various external forces, the maximum stress on the ligament in the normal model ranged from 1.949 to 18.302 MPa with an inconsistent distribution. In the all-inside reconstructed ACL model, the maximum stress on the graft ranged from 0.705 to 3.465 MPa, mainly at the junction of the graft and the tibial footprint. For the traditional reconstructed ACL model, the maximum stress on the graft ranged from 5.012 to 59.269 MPa, primarily at the junction of the interference screw and the graft. The stress on the loop and plate in the all-inside reconstructed model ranged from 70.461 to 346.363 MPa, with maximum stress at the junction of the loop and the tibial surface. In the traditional model, the maximum stress on the interference screw ranged from 10.184 to 92.298 MPa, with peak stress at the end of the screw. Conclusions: The graft in the all-inside ACL reconstruction is subjected to fewer external forces compared to the traditional reconstruction, suggesting a relatively stable mechanical environment. The strength of the loop and plate is sufficient to withstand daily knee joint movements without injury.